Синергија техничке и фундаменталне анализе у предвиђању прекограничних токова капитала и алокације средстава - Rongrodejanarug, Sorranan (Journal of process management and new technologies, 2024)
In an increasingly interconnected global financial landscape, investors seek effective strategies for managing portfolios across borders. This review paper examines the integration of Technical Analysis (TA) and Fundamental Analysis (FA) in forecasting cross-border capital flows, focusing on the unique contexts of Thailand, United Kingdom, and Japan. TA utilizes historical price data and indicators such as moving averages and Relative Strength Index (RSI) to inform short-term trading decisions (Murphy, 1999), while FA assesses the intrinsic value of securities based on economic indicators, financial health, and market conditions to guide long-term investment strategies (Graham & Dodd, 2009). By synthesizing existing literature, this paper highlights the theoretical frameworks that support the combined use of TA and FA, aiming to bridge the gap between immediate market movements and long-term economic fundamentals. The review identifies key studies that demonstrate the efficacy of integrating both approaches, suggesting that this combined methodology can enhance forecasting accuracy and improve investment outcomes. Through case studies of Thailand, United Kingdom, and Japan, the paper illustrates the practical applications of this combined analysis. In Thailand, local economic indicators and political events shape capital flows in the UK, macroeconomic factors such as Brexit and monetary policy play crucial roles and in Japan, unique market characteristics and technological advancements influence investor behavior. Ultimately, this review advocates for a holistic approach to investment analysis, emphasizing the need for further research into the synergistic effects of TA and FA in international portfolio management.